Maternal outcome in accreta cases. Conservative surgery and hysterectomy in Cipto Mangunkusumo General Hospital, Jakarta, Indonesia, from January 2017 to January 2018 - Fita Maulina; Mohammad Adya Firmansha Dilmy; Yudianto Budi Saroyo; Yuditiya Purwosunu (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHT1. As the incidence of placenta accreta is increasing which seems to parallel the increasing cesarean delivery rate, advance planning should be made for the management of delivery. 2. Maternal outcome of placenta accreta cases in a national hospital was reported based on the surgical technique performed.3. No significant results of maternal outcome undergoing conservative surgery and conventional hysterectomy in managing accreta cases in the national hospital.ABSTRACTObjectives: To report maternal outcome based on surgical technique on the management of accreta. The study was conducted in Cipto Mangunkusumo Hospital, Jakarta, Indonesia from January 2017 to January 2018.Case Report: There were 1609 cases of pregnant women delivered during the study period. From these, the prevalence of previous caesarean section was 73 cases, including 20 cases of accreta. Total maternal mortality for 1 year in Cipto Mangunkusumo Hospital, Jakarta, Indonesia, was 11, and accreta contributed 3 cases. We reported 20 cases of accreta in pregnancy The maternal outcomes, including bladder injury, duration of operation, intraoperative bleeding, length of hospitalization, and mortality, were evaluated. From 20 cases, 8 patients had one previous caesarean history, 11 had second previous caesarean section, while 2 patient had third previous caesarean section history. Of women with placenta accreta, about 7 patients (35%) had delivery in fullterm pregnancies, while 13 (65%) had delivery in preterm pregnancy. Surgical technique in accreta management mostly was hysterectomy to override bleeding complication along the delivery. From 20 cases, 16 caesarean sections were followed-up with hysterectomy. Four cases were with conservative management. From all the hysterectomy performed, four were complicated with bladder injury. The mean intraoperative bleeding was 600 - 5500 cc of blood, while the mean of post-operative transfusion was 1000 -3000 cc. There were 2 maternal deaths in this study. Thirteen patients were admitted to the ICU after the procedure.Conclusion: Accreta increases morbidity due to massive bleeding. It is important to have algorithm for managing abnormal implantation of the placenta. Our cases revealed no significant results of maternal outcome between conservative surgery and conventional hysterectomy in managing accreta cases in Cipto Mangunkusumo Hospital, Jakarta, Indonesia.